DIALOGUE AS A GENRE OF PHILOSOPHICAL TEXT - Корниенко, Александр (SWorldJournal, 2020)
The article analyzes the nature of philosophical dialogue as one of the main forms of philosophical writing. The author conducts such an analysis using the example of Plato’s dialogues, which are the pinnacle of this genre. The author highlights such feat